Ripening-Related Changes in Color and Bioactive Compounds of Diospyros kaki: Preliminary Insights on Its Antifungal Activity - Francesco Cairone; Letizia Angiolella; Francesca Bertini; Antonia Iazzetti; Giancarlo Fabrizi; Stefania Petralito; Stefania Cesa; Giovanna Simonetti (Foods)
Diospyros kaki L. is acknowledged for its extraordinary phytotherapeutic properties due to the presence of polyphenols, carotenoids, and flavonoids such as β-cryptoxanthin and rutin. These compounds are largely distributed in the skin and flesh of the fruit. In this study, the different parts of persimmons were analyzed (whole fruit, peels, and flesh), aiming at determining total carotenoid and flavonoid content through selective extraction and HPLC-DAD analysis. Obtained by a one-pot double phase extraction, organic and aqueous extracts were submitted to colorimetric analyses and tested for their antifungal activity. Results indicated that carotenoid and flavonoid content varied with sample maturity, and colorimetry proved to be an effective predictor of pigments’ composition. The strongest antifungal and antibiofilm activity has been demonstrated for the hydroalcoholic extracts of the unripe whole fruit and flesh. Preliminary results suggest their potential application in preventing Candida infections by inhibiting their establishment. Although further studies are needed, these results open the way to the possible use of the extracts as additives in foods or in the preparation of pharmaceutical formulations for the prevention of infections caused by Candida albicans, helping to reduce the use of synthetic biocidal products.